Validation of an Instrument on Bullying in Older Adults - Inmaculada Méndez; Isabel García-Munuera; Cecilia Ruiz-Esteban; José A. López-Pina (Clínica y Salud. Investigación Empírica en Psicología, 2025)

(untitled)
Background: The need to validate questionnaires that allow obtaining information about bullying in older people has become apparent. In Spain, no validated instrument adapted to this population has been found. The aim of this study was to validate a questionnaire to measure bullying situations among the elderly. Method: The study involved 475 elderly people aged 58 to 95 years, with an instrumental type design. The instrument consists of 22 items with Likert scale. The factor structure of the harassment questionnaire was determined with an exploratory factor analysis using the weighted least squares method. Results: Four factors were obtained. i.e., social exclusion victim, aggressor victim, verbal violence victim, and aggression-using-weapons victim and aggressor. Conclusions: The study suggests that bullying among older people exists and that it needs to be not only evaluated but also that measures for prevention and effective intervention be put in place.